A Constant Market Share Analysis of Spanish Goods Exports - González Pandiella, Alberto (OECD Publishing, 2015)
The constant market share analysis framework is used to decompose changes in Spain's share of the global market for goods exports into competitiveness and structural effects (i.e. the impact of specialisation, either in product or geographical terms) over 1996-2013. As other high-income countries, Spain has experienced competitive pressures from China and other emerging economies that have resulted in a loss of global market share. Nevertheless, the loss has been smaller than in other European advanced economies, thanks to better competitiveness. By contrast, the structure of geographic markets to which Spain exports, with a large-weight on relatively slow-growing areas and a small weight on fast-growing emerging countries, has exerted a negative impact on Spanish exports. In the same vein, the product structure, focused on relatively slow growing product lines, has not been conducive to better export performance either. This Working Paper relates to the 2014 OECD Economic Survey of Spain (http://www.oecd.org/eco/surveys/economic-survey-spain.htm)
Keywords: Economics; Spain